IMPLEMENTATION OF THE STATEâS RIGHT TO CONTROL IN THE CONTEXT OF AGRARIAN REFORM IN INDONESIA - Pratama, Ridho Ardian (Jurnal IUS, 2013)
The stateâs possession right regime has, in its application, brought up variety of interpretations. In relation with the implementation of agrarians reform in Indonesia, it is initially driven and led to be a primary instrument supporting such program. This research based on the fact that the stateâs possession right nowadays is not appropriately or properly used within the agrarian reform. One of the causes of such situation is the vagueness of the authority basis of the stateâs possession right. Up to now, the implementation of the agrarian reform as major agenda is still uncompleted. since new order ruling government, many regulations enacted are incompatible with the article 33 of Indonesian constitution of 1945, act of agrarian and act of land reform. Today, government has set up a national agrarian reform program which is basically and contextually different from which act of agrarian and act of land reform mandate. The huge thing to which people focusing their attention is both the interpretation and application of the stateâs possession right to assume has been employed in the wrong track, i.e. for the sake of investment, mining, industry and forestry.Keywords: The Stateâs Possession Right, The Agrarian Reform